2021
DOI: 10.1093/geronb/gbab073
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Crossers: How Providers Facilitate Ethnic Minority Families’ Access to Dementia Services

Abstract: Background Providers who work closely with ethnic minority people with dementia and their families are pivotal in helping them access services. However, few studies have examined how these providers actually do this work. Using the concept of ‘boundary crossers,’ this article investigates the strategies applied by these providers to facilitate access to dementia services for ethnic minority people with dementia and their families. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Most of the studies did not refer to a theoretical framework [ 6 , 16 20 , 22 – 35 , 37 39 , 41 , 43 ]. Only four studies [ 21 , 36 , 40 , 42 ] reported to have used a theoretical framework.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Most of the studies did not refer to a theoretical framework [ 6 , 16 20 , 22 – 35 , 37 39 , 41 , 43 ]. Only four studies [ 21 , 36 , 40 , 42 ] reported to have used a theoretical framework.…”
Section: Resultsmentioning
confidence: 99%
“…Ethnic aspects were addressed in eight studies as possible barriers to using care services [ 28 , 30 , 31 , 33 , 34 , 36 , 37 , 41 , 42 ]. Those barriers included family obligations, language barriers, and the lack of culture- and religion-sensitive support services.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Improved dementia knowledge can lessen the cultural perceptions of dementia and create a sense of belongingness for carers and families. This will be one step towards ensuring quality care for older immigrants with dementia, as Brijnath et al 57 noted that communicating clearly and empathetically with PWD and their families is important in reducing dementia stigma.…”
Section: Discussionmentioning
confidence: 99%